Trachyonychia and lichen sclerosus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 13-year-old boy was first observed due to nail lesions of the hands, dating from 9 months. The family history was positive for autoimmunity, because the paternal grandmother had thyroiditis, a maternal aunt had psoriasis and a first cousin, daughter of the aunt with psoriasis, was celiac. The physical examination put in evidence nails with irregular lamina, coarse, with longitudinal streaks, leading to the diagnosis of trachyonychia. Tazarotene gel 0.05% on the nail matrix and a urea-based cream on the nail plate was prescribed. After 3 months the nails had improved, but the boy told us that from about a year ago he was no longer able to pull back the foreskin and discover the glans. The physical examination showed a whitish ring (Fig. 2) that prevented the retraction of the foreskin. The urethral orifice was not compromise and there were no other skin lesions at extragenital sites. The final diagnosis was lichen sclerosus.